Exploring nature-based art therapy: a scoping review - Elīna Gulbe; Aija Ozola; Beāte Vītola; Elīna Akmane; Jasmina Pacek; Kristīne Mārtinsone (Frontiers in Psychology)
IntroductionNature-based art therapy is a therapeutic approach that uses natural elements and settings to promote well-being and health through creative expression, facilitated by a professional art therapist. Interest in nature-based mental health approaches surged, particularly following the COVID-19 lockdowns, as research highlights nature’s role in health restoration and sustainability. Despite growth in the field, a comprehensive overview of nature-based art therapy remains absent. This scoping review aimed to map the research landscape and identify the thematic scope within this emerging field.MethodsA systematic search following the PRISMA-ScR guidelines across the ProQuest, SAGE, Scopus, Taylor & Francis, and ScienceDirect databases identified 11 publications that address art therapy involving nature and are published in English.ResultsThe review identified four key themes: areas of focus, nature engagement, core elements, and challenges in nature-based art therapy. The areas of focus encompassed overall mental health and well-being, emotion regulation and stress management, cognitive development, social bond and support, self-discovery and personal growth, trauma and grief management, creative self-expression, and environmental sustainability. The core elements, such as artwork, materials, and therapy settings, were identified. Although nature-based therapy, involving both direct and indirect nature engagement, described promising benefits, specific challenges, including complexities in client assistance, constraints in nature access, psychosocial and cultural barriers, and risk management, were also highlighted.DiscussionThis scoping review provides a comprehensive framework for understanding nature-based art therapy and underscores the need for further theoretical and practical evidence-based development in this field.